The phase value of putamen measured by susceptibility weighted images in Parkinson's disease and in other forms of Parkinsonism: a correlation study with F18 FP-CIT PET. (July 2016) - Kwon, Gene Hyuk; Jang, Jinhee; Choi, Hyun Seok; Hwang, Eo-Jin; Jung, So-Lyung; Ahn, Kook-Jin; Kim, Bum-soo; Yoo, Ie Ryung; Kim, Sung Hoon; Haacke, E Mark
Background: Iron deposition of basal ganglia in Parkinson's disease (PD) can be measured using susceptibility weighted images (SWI) on magnetic resonance imaging (MRI). Fluoropropyl carbomethoxy-3b-4-iodophenyltropane (F18 FP-CIT) positron emission tomography (PET) has been used to differentiate Parkinsonism. Purpose: To compare SWI phase values in Parkinsonian syndrome and age-matched control and to correlate them with F18 FP-CIT PET. Material and Methods: Retrospectively, patients with Parkinsonian movement disorder ( n = 62) and age-matched control ( n = 16) were enrolled. Mean phase values on SWI were measured by region of interest (ROI) in putamens and caudate heads. Mean standardized uptake value (SUV) on F18 FP-CIT were measured in the same ROIs of PD ( n = 40) and other forms of Parkinsonism ( n = 22). A statistical analysis was performed to compare the phase values and SUVs and to correlate them between groups. Results: The putaminal mean phase values were higher in Parkinsonism than in the control ( P ≤ 0.001). There was no difference of phase value in caudate head among the groups. Also, the mean phase value of putamen between PD and other forms of Parkinsonism was not different. Mean SUV of F18 FP-CIT in the putamen was lower in PD than other forms of Parkinsonism ( P ≤ 0.014). However, there was no significant correlation between phase values and mean SUV ( P > 0.05). Conclusion: The putaminal phase value was higher than in Parkinsonian syndrome than in the age-matched controls. F18 FP-CIT PET/CT showed different tracer activity between PD and other forms of Parkinsonism. However, no correlation between phase and SUV values was discovered.